Association of TRPS1 gene with different EMT markers in ERα-positive and ERα-negative breast cancer - Su, Peng (BioMed Central, 2014)
BACKGROUND: Breast cancer is a heterogeneous disease consisting of different subtypes. Trichorhinophalangeal syndrome type 1 (TRPS1) gene, a GATA-type transcription factor, has been found to be highly expressed in breast cancer. Epithelial-to-mesenchymal transition (EMT) is known to play an important role in tumour invasion and metastasis. Our objective was to elucidate the different roles and clinical relevance of TRPS1 in different estrogen receptor (ER) expression subtypes of breast cancer. METHODS: An immunohistochemical study was performed. The correlation between clinicopathological features and other biomarker profiles were analysed statistically. RESULT: TRPS1 expression was correlated with the patients’ age (P = 0.017). It was positively related with ERα (P < 0.001), progesterone receptor (PR) (P < 0.001) and ERβ (P = 0.001) status, but negatively associated with Ki67 (P = 0.002) and HER2 (P = 0.025) status. In ERα-positive breast cancer, TRPS1 expression was positively associated with the expression of E-cadherin (P < 0.001), β-catenin(P = 0.001), ERβ (P = 0.03), and p53 (P = 0.002) status, while in ERα-negative breast cancer, TRPS1 expression was correlated with slug (P = 0.004), vimentin (P = 0.003), smooth muscle actin (SMA) (P = 0.031), and IMP3 (P = 0.005) expression. CONCLUSIONS: Based on our findings, we conclude that TRPS1 is positively associated with E-cadherin and β-catenin status in ERα-positive breast cancer cells, while it is also significantly associated with mesenchymal markers of EMT in ERα-negative breast cancer cells. TRPS1 can be a prognostic marker depending on the type of breast cancer. VIRTUAL SLIDES: The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/8686515681264281